2013
DOI: 10.1016/j.landusepol.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of natural amenity on farmland values: A quantile regression approach

Abstract: The objective of this study is to estimate the impact of natural amenity on farmland values in the contiguous United States using a quantile regression approach and data from the 2006, 2007, and 2008 Agricultural Resource Management Surveys. The contribution of this study is threefold. First, we explicitly include variables representing natural amenity, and soil characteristics of farmland. Second, we employ a quantile regression approach to examine potentially heterogeneous impacts of natural amenity and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 28 publications
(28 reference statements)
1
42
0
Order By: Relevance
“…The Least squares regression only measures how the changes in the vectors of the covariates affects the conditional mean function of . Furthermore, OLS regression is very sensitive to outliers, which may lead to inaccurate predictions due to the presence of multicollinearity, abnormal distribution and the independent nature of the residuals [43]. Moreover, QR is invariant to monotonic transformation which is different from OLS [40,43].…”
Section: Model Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Least squares regression only measures how the changes in the vectors of the covariates affects the conditional mean function of . Furthermore, OLS regression is very sensitive to outliers, which may lead to inaccurate predictions due to the presence of multicollinearity, abnormal distribution and the independent nature of the residuals [43]. Moreover, QR is invariant to monotonic transformation which is different from OLS [40,43].…”
Section: Model Estimationmentioning
confidence: 99%
“…Furthermore, OLS regression is very sensitive to outliers, which may lead to inaccurate predictions due to the presence of multicollinearity, abnormal distribution and the independent nature of the residuals [43]. Moreover, QR is invariant to monotonic transformation which is different from OLS [40,43]. In addition, QR is more robust to the non-normal error term and outliers in the model and takes into consideration the major effects of the covariates on the distribution of the dependent variable holistically and not only the conditional mean.…”
Section: Model Estimationmentioning
confidence: 99%
“…According to our definition, climate variables are also intrinsic characteristics, and their hedonic values for agricultural production can be elicited from land prices (Uematsu et al, 2013). Widespread use of the informational content of land price in terms of climate variables is related to the evaluation of climate change's effects on the agricultural sector.…”
Section: The Value Of Intrinsic Environmentmentioning
confidence: 99%
“…In Southern Michigan, Ma and Swinton, 2011, estimated the values of ecosystem services from the price of farmland, showing that such services are capitalized through variables related to ecological areas such as lakes, rivers, wetlands, forests and conservation land. In addition,Borchers et al, 2014, showed, for the US as a whole, that land prices are determined by the recreational and natural amenities provided by farmland, such as tree cover and hunting license Uematsu et al, 2013,. analyzed the value of a set of natural amenities and found that its impact is more pronounced at higher price range of farmland.…”
mentioning
confidence: 99%
“…3 This is, therefore, a more flexible approach than the conventional approach in the hedonic price function estimation. The studies done by Zietz et al (2008), Heintzelman (2010) and Uematsu et al (2013), for instance, have applied a quantile regression model for this purpose. The commonality of these studies is to show the marginal effects of housing characteristics under different price quantiles.…”
mentioning
confidence: 99%